Proceed with Caution: Law Reform, Judicial Review and the Judicature Modernisation Bill - Watkins, Morgan (Victoria University of Wellington Law Review, 2016)
The Judicature Modernisation Bill 2013 re-enacts the operative provisions of the Judicature Amendment Act 1972. This article analyses the re-enacted provisions, concluding that the reform will be largely successful relative to a goal of "non-substantive reform". However, this article argues that there were significant defects in the legislative process leading to reform, especially in terms of parliamentary scrutiny of judicial review. In a context of a fused executive–legislative branch of government, it is inappropriate to legislate for judicial review without adequate consideration of the effects on judicial review powers and processes. This article argues that judicial review procedure should not be contained in statute in order to prevent executive control of the statutory review procedure.